Effect of PC6 Nei Guan and ST36 Zu San Li Acupressure on Nausea and Vomiting Frequency in Pregnancy - Zaiyina Nurkamila; Susanti Pratamaningtyas; Indah Rahmaningtyas; Eny Sendra (Borneo Nursing Journal (BNJ), 2026)
Nausea and vomiting of pregnancy (NVP) are common complaints caused by increased levels of hCG and estrogen hormones, which may lead to dehydration, nutritional disturbances, stress, and decreased quality of life. Acupressure at the PC6 and ST36 points is a non-pharmacological therapy that has the potential to reduce these symptoms. This study aimed to analyze the effect of PC6 and ST36 acupressure on the frequency of nausea and vomiting among first- and second-trimester pregnant women. This study employed a pre-experimental design with a one-group pretest-posttest approach. The population consisted of 30 pregnant women at Sukorame Public Health Center, Kediri City, and 28 samples were obtained using a consecutive sampling technique. The frequency of nausea and vomiting was measured using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) instrument and analyzed using the Wilcoxon Signed Rank Test. The results showed a significant decrease in nausea and vomiting scores after the intervention, with an Asymp. Sig. (2-tailed) value of (0.000) < α (0.05). After the intervention, most respondents were in the mild category, totaling 19 respondents (67.9%). It can be concluded that acupressure at the PC6 and ST36 points was effective in reducing nausea and vomiting during pregnancy.